Propostas terapêuticas para o mastocitoma canino baseadas em fatores prognósticos clínicos, anátomo-patológicos, imuno-histoquímicos e genéticos - Rodrigo dos Santos Horta (2016)
The objective of this thesis was to evaluate the effectiveness of prognostic factors and different therapeutic approaches towards canine mast cell tumour, considering its high incidence and heterogeneity in clinical presentation and biological behavior, representing a guideline for prognosis and treatment. It included dogs referred to the Veterinary Hospital (Universidade Federal de Minas Gerais, Brazil) and Queen's Veterinary School Hospital (University of Cambridge, United Kingdom), with histological diagnosis of mast cell tumour. Evaluated prognostic factors included clinical, histological, immunohistochemical and genetic features, resulting in five distinct studies. Study 1 (n = 62) demonstrated high response rate to glucocorticoids (64.5%) in the treatment of measurable disease, and showed a negative impact on prognosis in the absence of response to these drugs. In study 2 (n = 149), the importance of different prognostic factors was evaluated, with a proposal of a modification for the World Health Organization´s recommended clinical staging, definition of new cut-off values for mitotic index and Ki-67. Study 3 (n = 98) showed the benefit of chemotherapy at maximum tolerated dose, in the control of high-risk mast cell tumours, while the study 4 (n = 21) demonstrated a high efficacy of adjuvant radiotherapy in the long-term control, of mast cell tumours of intermediate risk. Finally, it was demonstrated in the study 5 (n = 31), the effectiveness of tyrosine kinase inhibitors in patients at high risk, in the treatment of gross, unresectable disease, but also in the adjuvant setting, although the use of glucocorticoids and antineoplastic agents may compromise such response.